Below‐ground plant–soil interactions affecting adaptations of rice to iron toxicity. (24th October 2021) - Kirk, Guy J. D.; Manwaring, Hanna R.; Ueda, Yoshiaki; Semwal, Vimal K.; Wissuwa, Matthias
Abstract: Iron toxicity is a major constraint to rice production, particularly in highly weathered soils of inland valleys in sub‐Saharan Africa where the rice growing area is rapidly expanding. There is a wide variation in tolerance of iron toxicity in the rice germplasm. However, the introgression of tolerance traits into high‐yielding germplasm has been slow owing to the complexity of the tolerance mechanisms and large genotype‐by‐environment effects. We review current understanding of tolerance mechanisms, particularly those involving below‐ground plant–soil interactions. Until now these have been less studied than above‐ground mechanisms. We cover processes in the rhizosphere linked to exclusion of toxic ferrous iron by oxidation, and resulting effects on the mobility of nutrient ions. We also cover the molecular physiology of below‐ground processes controlling iron retention in roots and root‐shoot transport, and also plant iron sensing. We conclude that future breeding programmes should be based on well‐characterized molecular markers for iron toxicity tolerance traits. To successfully identify such markers, the complex tolerance response should be broken down into its components based on understanding of tolerance mechanisms, and tailored screening methods should be developed for individual mechanisms. Abstract : Progress in identifying markers for Fe toxicity tolerance in rice has been slow because of the complexity of tolerance mechanisms and the importance of below‐ground plant‐soil interactions. We review current understanding of these below‐ground processes, including recent advances in the molecular physiology of tolerance.